PERHITUNGAN UANG TEBUSAN DAN PERLAKUAN TERHADAP HARTA WARISAN DALAM TAX AMNESTY DI INDONESIA - Rudeva Juniawaty (Sosio e-Kons, 2016)
In the middle of 2016 tax amnesty began hotly discussed in the wider community, especially the taxpayer, the taxpayer individuals and micro enterprises. Many are questioning the purpose enactment of tax amnesty and anything that can be included in a tax amnesty program and anyone who had follow. For taxpayer whose tax adminstration is not in accordance with the law of taxation, following the tax amnesty will be very beneficial as avoid fines and tax penalties. But not all taxpayer understand the tax amnesty, anything and anyone who can follow the tax amnesty program. Through this article the authors try to explain the tax amnesty, so that the taxpayer can determine the objects that can be included in a tax amnesty program and whether it should follow the tax amnesty or simply report the last year income tax.Keyword:Tax Amnesty, UU No 11 Tahun 2016